Civil rights in American law, history, and politics / edited by Austin Sarat, Amherst College. - Sarat, Austin (Cambridge University Press, 2014)
Civil Rights in American Law, History, and Politics charts the ambiguous and contested meanings of civil rights in law and culture and confronts important questions about race in contemporary America. How important is civil rights in America's story of possibility and change? How has it transformed the very meaning of citizenship and identity in American culture? Why does the subject of race continue to haunt the American imagination and play such a large role in political and legal debates? Do affirmative action and multiculturalism promise a way out of racial polarization, or do they sharpen and deepen it? Are there new and better ways to frame our commitment to equal justice? This book brings together the work of five distinguished scholars to critically assess the place of civil rights in the American story. It offers different ways of talking about civil rights and frames through which we can address issues of civil rights in the future.